Evaluation of prescription pattern of antifungal drugs in the dermatology department of a tertiary care teaching hospital - Kalola, Abhishek S.; Shah, Shreya M.; Mistry, Chirag B. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: In general, fungal infections are one of the contributors of disease burden in the community, but irrational use of antifungal drugs can result in unwanted adverse events or antifungal drugs resistance. The present study was designed to analyze the prescription pattern of antifungal drugs prescribed in the dermatology department of a tertiary care teaching hospital. Methods: After getting permission from the ethics committee, this prospective observational cross-sectional study was conducted by analysis of prescriptions of 900 voluntary participant patients over a period of seven months in the dermatology outpatient department of a tertiary care teaching hospital in western India. Prescribed medicines’ parameters were analyzed as per WHO/INRUD prescription indicators. Results: Overall 900 prescriptions were analyzed, and among them around 50% patients were having tinea corporis and tinea cruris, making it the most common fungal infection. The most commonly prescribed antifungals were Clotrimazole (34.59%), followed by Fluconazole (31.61%) and Luliconazole (23.52%). Percentage of drugs prescribed from the WHO model list of essential medicines was 71.22%. Average number of antifungal drugs per prescription was 2.83 ± 0.57%. Conclusions: This study indicates prescribing practices of anti-fungal drugs and supportive medicines at tertiary care hospital that can be further improved by promoting prescribing by generic names. Overall final list of essential medicines at district level, state level and national level may vary as compared to the WHO list for anti-fungal drugs and doctors can consider alternative drugs as per domestic resistant pattern.